Materials for supercapacitors: When Li-ion battery power is not enough. Issue 4 (May 2018) - Lin, Z.; Goikolea, E.; Balducci, A.; Naoi, K.; Taberna, P.L.; Salanne, M.; Yushin, G.; Simon, P.
Graphical abstract: Abstract: Supercapacitors, also known as electrochemical capacitors, have witnessed a fast evolution in the recent years, but challenges remain. This review covers the fundamentals and state-of-the-art developments of supercapacitors. Conventional and novel electrode materials, including high surface area porous carbons for electrical double layer capacitors (EDLCs) and transition metal oxides, carbides, nitrides and their various nanocomposites for pseudocapacitors – are described. Latest characterization techniques help to better understand the charge storage mechanisms in such supercapacitors and recognize their current limitations, while recently proposed synthesis approaches enable various breakthroughs in this field.